The feature's informational value of the collectional melon’s samples - І. М. Бобось (Plant Varieties Studying and Protection)
It was marked out the correlating the feature's groups of sample’s collection of melon with two levels of correlation (r ? 0,50 і r ? 0,75), which give the possibility to assess the samples by one of the feature that facilitates significantly the analysis of information in the collection of the seed-plot.